2021
DOI: 10.1097/der.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing to Carvone: North American Contact Dermatitis Group Experience, 2009 to 2018

Abstract: Background/Objectives: Carvone, a flavoring agent, may cause allergic contact dermatitis. This study summarizes patch test reactions to carvone in patients tested by the North American Contact Dermatitis Group, 2009 to 2018.Methods: This was a retrospective analysis of patients positive to carvone (5% petrolatum). Demographics were compared with those of patients who were negative. Other analyses included reaction strength, clinical relevance, coreactivity with other fragrance/flavor allergens, and exposure so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
2
10
1
Order By: Relevance
“…As carvone and limonene are chemically related, an association between carvone and oxidised limonene would not be surprising. However, in previous studies, only a small number of patients sensitised to carvone also reacted to oxidised limonene, 13 , 15 and in the present study only a weak association between hydroperoxides of limonene and carvone was found. Furthermore, a significant part of the carvone‐positive patients (64%) did not have a concomitant allergy to a fragrance/flavour substance, and 44% of those with a clinically relevant carvone allergy would have been missed if not tested with carvone.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…As carvone and limonene are chemically related, an association between carvone and oxidised limonene would not be surprising. However, in previous studies, only a small number of patients sensitised to carvone also reacted to oxidised limonene, 13 , 15 and in the present study only a weak association between hydroperoxides of limonene and carvone was found. Furthermore, a significant part of the carvone‐positive patients (64%) did not have a concomitant allergy to a fragrance/flavour substance, and 44% of those with a clinically relevant carvone allergy would have been missed if not tested with carvone.…”
Section: Discussioncontrasting
confidence: 92%
“…In an earlier study, concomitant allergy to sesquiterpene lactone mix was common, 8 , 14 but in our study and in the recent North American study, this was uncommon. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Several cases of cheilitis and lichen planus from carvone in toothpaste have been described 1,4 . Only 1 case of carvone-associated orofacial granulomatosis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Women (76.1%) were common in the carvone-positive group. 148 Quertermous and Fowler also described that a woman used a hair conditioner with a mint scent, and the dermatitis resolved when she stopped using this product. 149…”
Section: Side Effects and Toxicitymentioning
confidence: 99%